CRITICAL ANALYSIS OF HARNESSING HEALTH INFORMATICS TECHNOLOGY FOR DATA-DRIVEN DECISION-MAKING IN ENHANCING EFFICIENCY AND QUALITY OF HEALTHCARE SERVICES - HAMAD MASOUD MANA AL YAMI, HUSAIN MANAN ALI AL ZAMANAN, NAJI KHAMIS SALEH ALHAMAMI, NAJI SALM NAJI ALHAMAMI, MOHAMMED ALI HASSAN ALHAMAMI, ABDLLAH SALEM ABDLLAH ALHMMAMI, (Chelonian Research Foundation, 2022)
Health informatics technology has changed the face of healthcare delivery totally with data-driven tools, which contribute to making outcomes better for both patients and providers by making the healthcare delivery process faster and more efficient. This paper critically focuses on the use of health informatics technology in healthcare, investigating its role in knowledge-making processes and effectiveness. A comprehensive literature review describes and evaluates different health informatics technology applications, methodologies, and scientific achievements. The procedure for data collection is described, as are the methods of analysis. Finally, the presentation of outcomes is presented in terms of figures, tables, and graphs. The conversation mentions the core points and lessons learned in the end, which summarize the recommendations on capitalizing on health informatics technologies to streamline healthcare delivery. Keywords: informatics relating to health, technology, utilizing data to make decisions, efficiency, quality, and improving healthcare services.